2021
DOI: 10.1161/jaha.120.019559
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Testosterone and Luteinizing Hormone With Blood Pressure and Risk of Cardiovascular Disease in Middle‐Aged and Elderly Men

Abstract: Background The age‐related decline in testosterone levels is thought to be of great importance for male aging and cardiovascular diseases. However, data are controversial on whether abnormal sex hormones are linked to the presence of cardiovascular diseases and it is also uncertain how blood pressure modifies the association between testosterone levels and major cardiovascular diseases. Methods and Results This is a multicenter, population‐based, cross‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 53 publications
1
15
1
1
Order By: Relevance
“…The prevalence of low testosterone (total T<11.1nmol/L) in men over 60 is about 20% (30), and low T is associated with insulin resistance, hypertension, and CVD (31,32). The Multivariable logistic regression analysis between sex hormones and HUA, after adjusting for variables (except for the grouped variables) such as age, BMI, WC, HT, DM, MS, CKD, CVD, HLP, eth, PA and alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of low testosterone (total T<11.1nmol/L) in men over 60 is about 20% (30), and low T is associated with insulin resistance, hypertension, and CVD (31,32). The Multivariable logistic regression analysis between sex hormones and HUA, after adjusting for variables (except for the grouped variables) such as age, BMI, WC, HT, DM, MS, CKD, CVD, HLP, eth, PA and alcohol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, patients with pituitary deficiency at admission accounted for 56.89% in the non-hemorrhage group and 83.33% in the hemorrhage group. Furthermore, it was reported that in men with severe hypertension, primary hypogonadism may be a risk factor of major cardiovascular diseases ( 31 ). Decreased LH may affect the vascular tissue and provoke bleeding by the extragonadally expressed lutropin/choriogonadotropin receptor (LHR) ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…In some observational studies an inverse correlation between testosterone serum levels and blood pressure or CVD risk has been shown (8,9). Qu et al (6) in a population-based, crosssectional study on 6296 men reported an inverse correlation between testosterone (total, free testosterone, and sex hormonebinding globulin) levels and the prevalence of hypertension or CVDs. Age > 65 years and body mass index > 24 negatively impacted the inverse association between testosterone and hypertension (Table 1).…”
Section: Cardiovascular Morbidity and Testosterone Castration Levelsmentioning
confidence: 98%
“…The age-related decline in testosterone serum levels in men has been described as a possible cause for the increased risk of hypertension and cardiovascular diseases (CVD). Testosterone can activate both vasodilator and vasoconstrictor pathways, but it is more pro-hypertensive in different models (6). Testosterone is also an anabolic hormone promoting muscle mass, fat loss, and therefore low levels of testosterone can be associated with a metabolic syndrome involving obesity and hypertension (7).…”
Section: Cardiovascular Morbidity and Testosterone Castration Levelsmentioning
confidence: 99%